2013
DOI: 10.1158/1078-0432.ccr-13-0190
|View full text |Cite
|
Sign up to set email alerts
|

Targeting FGFR with Dovitinib (TKI258): Preclinical and Clinical Data in Breast Cancer

Abstract: Purpose: Fibroblast growth factor receptor 1 (FGFR1) and FGFR2 amplifications are observed in approximately 10% of breast cancers and are related to poor outcomes. We evaluated whether dovitinib (TKI258), an inhibitor of FGFR1, FGFR2, and FGFR3, presented antitumor activity in FGFR-amplified breast cancers.Experimental Design: Preclinical activity of dovitinib was evaluated in both breast cancer cell lines and an FGFR1-amplified xenograft model (HBCx2). Dovitinib was then evaluated in a phase II trial that inc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
238
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 290 publications
(248 citation statements)
references
References 24 publications
7
238
0
3
Order By: Relevance
“…31 Recent publications demonstrated with in vitro experiments, mouse models and clinical trials that Dovitinib showed antitumor activity in FGFR-amplified breast cancer. 34 The effect of Dovitinib observed included blocking breast cancer cell proliferation and growth, inhibiting tumor metastatic speed of breast cancer in vivo and in vitro models. 15,35 Co-targeting of ErbB receptors enhanced those effect of Dovitinib, since this 2 receptor tyrosine kinases have same downstream signaling PI3K/Akt/ mTOR and the anti-tumor effect resulted from the blockade of receptor tyrosine kinases by Dovitinib was shown mostly via PI3K/Akt/mTOR signaling inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…31 Recent publications demonstrated with in vitro experiments, mouse models and clinical trials that Dovitinib showed antitumor activity in FGFR-amplified breast cancer. 34 The effect of Dovitinib observed included blocking breast cancer cell proliferation and growth, inhibiting tumor metastatic speed of breast cancer in vivo and in vitro models. 15,35 Co-targeting of ErbB receptors enhanced those effect of Dovitinib, since this 2 receptor tyrosine kinases have same downstream signaling PI3K/Akt/ mTOR and the anti-tumor effect resulted from the blockade of receptor tyrosine kinases by Dovitinib was shown mostly via PI3K/Akt/mTOR signaling inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…It has shown promising results in CRC with KRAS mutated because of increased expression of FGFR1 when compared to CRC BRAF mutated (increased expression of FGFR3) . In breast cancer, Dovitinib demonstrated anti-tumor activity in FGFR-amplified breast cancer cell lines (André et al, 2013). In advanced thyroid cancer the commonest treatmentrelated adverse events were diarrhoea, anorexia, vomiting, fatigue and nausea, most of which were grade 1 or 2 (Lu et al, 2008c).…”
Section: Non-selective Fgfr Tkismentioning
confidence: 99%
“…Иммунотаргетные препараты могут быть полезны, имеются последние данные в отношении ингибирова-ния PD-1 [63][64][65] Палбоциклиб, ингибитор CDK 4 / 6, в комбинации с летрозолом показали превосходную клиническую эффективность по сравнению с одним летрозолом в рандомизированном исследовании II фазы PALOMA-l / TRIO-18 [66] Таргетные пути репарации ДНК У пациентов с дефицитом репарации ДНК, связанным с мутацией генов BRCA1 или BRCA2, была показана высокая частота pCR на химиотерапию препаратами платины [67,68]. Карбоплатин оказался более активным, чем доцетаксел, у пациентов с метастатическим РМЖ и мутацией BRCA [68] Таргетный путь PI3K Сочетание BYL719 (специфического ингибитора PIK3CA-α) и фулвестранта продемонстрировало синергетический эффект на доклинических моделях [69] Таргетный путь FGFR Предварительные исследования ингибиторов FGFR довитиниба [70] и люцитиниба [71] продемонстриро-вали многообещающую частоту ответов, но выраженную токсичность обоих препаратов Генетические особенности Тамоксифен снижает риск рака контралатеральной молочной железы у пациентов с мутациями генов BRCA1 и BRCA2 при ER-положительных или ER-отрицательных опухолях [72] Первичная профилактика Последние данные подчеркивают роль предшествующей доброкачественной патологии с наличием атипии или без (но в меньшей степени) как фактора риска возникновения РМЖ [73] Тестирование на ER и PR Опыт некоторых учреждений показывает, что сомнительное значение окрашивания ER (от 1 до 9 %) чаще наблюдается у молодых пациентов с опухолями высокой степени злокачественности или при HER-2-позитивных или PR-негативных опухолях. При этом более точный прогноз в отношении безрецидивной выживаемости отмечается при ER-отрицательных опухолях [74].…”
Section: внутренние подтипыunclassified